Geo-Marine Letters An International Journal of Marine Geology - Uenzelmann-Neben, Gabriele; Bryan, Karin; Green, Andrew; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Geo-Marine Letters is an international peer-reviewed journal focussing on the rapid publication of concise original studies and reviews dealing with processes, products and techniques in marine geology, geophysics, and geochemistry. Coverage spans - structural geology, including plate tectonics of recent active and passive margins - sea-bed morphology, physiography and morphodynamics - sediment transport, depositional processes and sedimentary facies analysis - stratigraphy, basin analysis and paleoenvironmental reconstruction - sea-level history, paleoproductivity, gas hydrates, salt domes and brines - sediment-water interaction and organism-sediment relationships - geochemical tracers, stable isotopes and authigenic mineral formation - geotechnical properties and application of new geo-marine techniques, and more. In addition to regular articles, reviews, discussion/reply articles and technical papers, Geo-Marine Letters welcomes contributions by guest editors in the form of conference/workshop proceedings, or bundles of papers dealing with specific themes. .
Keywords: Geology; Geology